Spiritualityd … Spirituality in our time – In conversation with Hartmut Rosa"s theory on social acceleration - Lombaard, Christoffel (HTS teologiese studies, 2018)
Based on a public lecture held at the University of Pretoria in September 2017, the first section of this article highlights experience as a turnkey to the post-secular mind frame, with transforming wholeness as an implicit objective of spirituality. The second illustrates some possibilities of diverse spiritualities through practical, experiential examples. Given that post-secularism is understood to be a new cultural mind frame on religiosity arising in our time and that spirituality is never context-free, the newest of sociological theories on time, and on our time, are indicated in the third and last section of this article. Helmut Rosa’s contribution in this regard is summarised, from which certain questions are teased out on spirituality.